PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ICT DAN PERSEPSI SISWA TENTANG METODE MENGAJAR GURU TERHADAP HASIL BELAJAR IPS TERPADU - Eka Romada; Tedi Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
The result of learning is the outcome obtained after attending learning activities in the form of scores or numbers which is gotten by a test. To achieve optimal learning result, students should explore their potential which comes from inside and outside the student. In addition, learning outcomes are also influenced by the potential of the student a desire to learn and motivation to study. Therefore, the low score of student learning outcomes is caused by the lack of use of ICT in the teaching learning activity and the lack of varied methods which is used by the teacher in the teaching learning activity. Based on preliminary research conducted at SMP Negeri 1 way tenong note that overall student learning outcomes in integrated social science study is low. In general, the things that affect the level of learning outcomes are divided into two factors, namely internal and external. Among the many factors that can affect or contribute to the achievement of student learning outcomes, factors suspected use of media and ICT learning teaching methods teachers have an important role. The purpose of this study were: (1) To determine the effect of the use of instructional media ICT on learning outcomes integrated IPS. (2) To determine the effect of students 'perceptions of teachers' teaching methods on learning outcomes integrated IPS. (3) To determine the effect of the positive use of media and ICT learning students 'perceptions of teachers' teaching methods on learning outcomes integrated IPS RSBI of the students in the first grade of SMP Negeri 1 Way Tenong West Lampung in the 2012/2013 academic year. The sampling technique is simple random sampling by using the formula T. Yamane come by as many as 71 students. The method which is used in this research is descriptive verification by using ex post facto and survey. The results showed that there is the influence of using ICT and perceptions of students about teaching methods which are used by the teacher toward learning outcomes of integrated social science study of first smester students in the first grade of SMP Negeri 1 Way Tenong West Lampung in the 2012/2013 academic year, Based on the analysis of data obtained F count 20.893 3.98 F table is addressed by multiple linear regression obtained R2 = 0.381 at a significance level of 0.05, which means that the learning outcomes are influenced by the activity of learning and teaching methods of teachers in schools of 38.1%.